Symbolic and Socioeconomic Responses of Families to Early Neonatal Indicators of Autism Spectrum Disorder: A Qualitative Study - Melaya, Putu; Juraid, Juraid; Sabir, M.; Nuraisyah, Nuraisyah (Journal of Neonatal Surgery, 2025)
The early identification of Autism Spectrum Disorder (ASD) remains a significant challenge, particularly in resource-limited settings where diagnostic infrastructure is lacking. This study explores how families interpret and respond to early signs of ASD observed during the neonatal period, explicitly focusing on symbolic interactions and socioeconomic factors. Using a qualitative approach grounded in symbolic interactionism, data were gathered through in-depth interviews with parents of children later diagnosed with ASD. Though subtle, the findings reveal that early behavioural cues often evoke emotional confusion, cultural interpretations, and varying parental denial or acceptance. Cultural norms, prior knowledge, and access to healthcare strongly influenced the symbolic meanings attributed to neonatal behaviours. Simultaneously, the financial strain from seeking consultations, therapies, and specialised care often heightened psychological stress within the household. The study highlights a crucial gap in early awareness and intervention pathways for ASD, especially in low- and middle-income countries. It calls for improved neonatal screening methods, culturally sensitive counselling, and socioeconomically inclusive support systems. Understanding how families symbolically construct and economically navigate their experiences with early ASD indicators can inform more holistic and empathetic neonatal care models.